ARUS KAS SEBAGAI ALAT BANTU UNTUK MENGUKUR LIKUIDITAS PERUSAHAAN Studi kasus Koperasi XXX - Evaf Maulina (JURNAL MITRA MANAJEMEN, 2021)
AbstractHigh Koperasi XXX operating costs have a relationship with Koperasi XXX decreased liquidity level. An increase in Koperasi XXX amount of debt has something to do with a decrease in KOPERASI XXX level of liquidity. The low amount of Koperasi XXX capital has a relationship with the decrease in Koperasi XXX level of liquidity.